Combining ability for various parameters in sunflowers as a classical breeding approach for superior hybrid development: Combining ability for various parameters in sunflowers as a classical breeding approach for superior hybrid development - YUKTA SHARMA; VINEETA KAILA; PANKAJ SHARMA (Journal of Oilseeds Research, 2023)
An experiment for estimating the combining ability in sunflower for various agronomic traits and oil content was carried out in 2021-22 at Punjab Agricultural University, Ludhiana, in which 91 hybrids were studied along with their parents, i.e., seven CMS lines and 13 high oleic testers. Significant positive and negative variations were noticed in GCA and SCA for characters like days to flowering initiation, fifty per cent flowering, plant height, head diameter, seed yield per plant and oil content. Dominant gene action was predominant for all these characters and high SCA was observed for high GCA × high GCA for flowering initiation, head diameter, and seed yield per plant and low GCA × high GCA for fifty per cent flowering, plant height and both high GCA × high GCA and low GCA × low GCA for oil content.